Incremental model synchronization for multiple updates - Giese, Holger; Hildebrandt, Stephan (International Conference on Software Engineering 2008, 2008)
One required capability to make the vision of model-driven software development reality is, that changes in the models can be consistently propagated between the different related models. In this paper, we present how our model synchronization algorithm based on triple graph grammars, presented in [11], can be improved, such that it outperforms batch processing also in case of multiple updates. We present an evaluation of our improvement, demonstrating that we can keep the speedup for the incremental processing in the average case for smaller numbers of changes, while accelerating the synchronization for larger numbers of changes. The improved algorithm is at least as fast as the batch algorithm.